Waste marble powder/dust - Demirel, Bahar; Alyamaç, Kürşat E. (Elsevier, 2018)
One of the most important parts of the mining industry is the marble industry. The use of marbles in the structures dates back to ancient times. However, especially in the last decades, the use of marble in the structures has increased too much. As the production in the marble factories increases, the amount of waste has reached a volume that cannot be stored. Marble wastes are formed as a result of cutting and polishing processes in marble factories. These by-products, which cannot be stored, should be utilized in other sectors. So, both economic losses can be reduced and environmental pollution can be prevented. In this chapter, firstly, the occurring process of the waste marble powder (WMP) is briefly explained. Moreover, then, the physical and chemical properties of WMPs that used in the different studies in the literature are presented. The fresh, strength, and durability properties of conventional and self-compacting concrete (SCC) produced by replacing with WMP were investigated in comparison with the literature. It has been observed that the use of WMP by replacing with cement or sand in both conventional and SCC positively affects fresh and hardened properties of these concretes. The use of WMP instead of raw materials (e.g., sand, coarse aggregate) obtained from the natural resources reduces the energy consumption and the use of these natural resources. As a result, it is possible to obtain economical and eco-efficient concretes using WMP. © 2018 Elsevier Ltd. All rights reserved.
Keywords: Concrete; Eco-efficient concrete; Marble sludge; Marble slurry; Self-compacting concrete; Waste marble dust; Waste marble powder